Pedagogical Approaches and Challenges among Teachers in the Implementation of the K-12 Curriculum in the Division of Maguindanao I - Alton D. Ampang (RIRAI Publisher, 2023)
The purpose of this study was to identify the pedagogical strategies employed by the teachers and their difficulties in implementing the K–12 curriculum in the Division of Maguindanao–I for the School Year 2017–2028. It aimed to respond to two questions in particular: In applying the K–12 curriculum framework in their classrooms, teachers used a variety of pedagogical strategies. How much did these strategies differ from one another? How many problems did they encounter? It used a descriptive survey design and a quantitative methodology. 75 respondents were chosen at random to receive survey questionnaires, and they were chosen from a pool of respondents. The study revealed that the high school teachers from the chosen secondary schools in Maguindanao-I division occasionally used pedagogical approaches in their instruction and occasionally encountered difficulties implementing the K–12 curriculum in the schools where they were assigned, particularly regarding the use and accessibility of ICT and teaching aids, which are seen as being crucial to providing students with high-quality education. This further demonstrated that teachers in public schools lacked the necessary pedagogical tools to effectively teach the K–12 curriculum. With this new trend in education, teachers still need to be prepared. However, teachers were still having trouble putting the new curriculum into practice. The most difficult component for the teachers has been utilizing ICT and ICT-related educational resources. This is due to the fact that some teachers still struggle to utilize computers effectively, and some pupils still struggle with subject matter understanding among professors.